The lost girls of Willowbrook - Wiseman, Ellen Marie (New York, NY : Kensington Publishing Corp., 2022)
"Six years after her twin sister's death, 16-year-old Sage discovers a shocking secret, her sister didn't die, she was committed to Willowbrook State School until she recently went missing, and, determined to find her, Sage walks through its doors, which changes her life in ways she never could have imagined."--
"Reading group guide"--Page 4 of cover
Keywords: Twin sisters -- Fiction; Reformatories -- Fiction; Missing children -- Fiction; Psychological fiction